Effect of Varying Amounts of Dry Yeast and Acetic Acid on Japanese Quail Some Carcass Traits - Taleb, Hassan Mohamad (Journal of agricultural, environmental and veterinary sciences, 2022)
The study was carried out on 180 chicks of Japanese quail in the poultry of ALNour –Jerrod- Syria, the birds were distributed from the beginning of the experiment into (9 groups at a rate of 20 chicks for each group, and each group was distributed into two repeats each repeating 10 chicks) of one-day old. All the conditions of shelter and care were the same for all groups during the care period, which lasted from the age of one day to the age of 6 weeks. As for the feeding of the birds of the different groups, they were different as follows: It included nine feed mixtures, each one differing from the other with the level of addition of dry yeast and the level of addition of vinegar acid (Three levels of dry yeast and three levels of acetic acid and the interaction between them to study their effect on Japanese quail some carcass traits) (3 x 3). • The first factor: the effect of the level of crude protein in mixtures, as it decreased and raised by 10% than it was in (NRC1994). • The second factor: is the effect of the level of dry yeast in the mixtures, as in the following proportions (0.0- 0.05- and 0.1%). The search is (3 × 3). The results of the research showed the following: • Effect of adding dry yeast: the addition of dry yeast in mixtures resulted in a significant superiority with: live body weight, body weight after slaughter, body weight after slaughter and tweezing, breast, dressing percentage, meat yield percentage, meat to bone ratio. • The effect of adding acetic acid: adding acetic acid to the mixtures resulted in a significant superiority: live body weight, body weight after slaughter, body weight after slaughter and tweezing, breast, dressing percentage, meat yield percentage, meat to bone ratio. • The effect of the interaction between dry yeast and vinegar acid: The interaction is positive when using dry yeast and acetic acid, as it gave the best Muscle yield and increases indicators of carcass characteristics.